Taxonomia integrativa do gênero Knodus Eigenmann, 1911 (Characiformes: Characidae) nas Bacias dos rios Mearim e Munim, Estado do Maranhão, Nordeste do Brasil - AGUIAR , Rayane Gonçalves (2021)
The Order Characiformes has the higher number of species of aquatic fauna, approximately 4,000, distributed in 24 families of neotropical fishes. Characidae is the most diverse and problematic family within the Characiformes. As an example of these taxonomic problems we can mention the genus Knodus, whose diagnosis, the presence of scales covering the caudal fin rays, is a source of discussion regarding the validity of the genus. One way to overcome the confusing taxonomy of problematic groups is to use multiple operational criteria for species delimitation, which produce more robust hypotheses of lineage divergences, converging on the proposal of an Integrative Taxonomy. The objective of this work was to carry out a taxonomic study, based on morphological and molecular data, on populations of the genus Knodus that occur in the basins of the Mearim and Munim rivers located in the State of Maranhão, Northeastern Brazil, based on different and independent methods of species delimitation. As a result of this work, the type locality of Knodus victoriae was updated. Misinterpretations in old descriptions and the change name of the municipality Vitória to Alto Parnaíba caused confusion on the exactly type locality of these species. Thus, based on bibliographical research, information on the expedition's intinerary, maps, diary and collections in the municipality, the type locality of these species was updated to the mouth of a stream that flows into the Parnaíba river, in the municipality of Alto Parnaíba in the State of Maranhão, upper Parnaíba river basin, northeastern Brazil. Type localities corrections and update are important to avoid taxonomic and biogeographic confusion. In addition, based on several methods using both morphological and molecular data, a new species of Knodus is herein described for the Mearim and Munim river basins. Although this new species has some similar characteristics, it differs from Knodus victoriae by having more total vertebrae, more branched and unbranched anal-fin rays and fewer circumpenducular scales. Molecular analyzes (WP, GMYC, bPTP, ABGD) were congruent in the delimitation of the new species with an average genetic distance of 14% from other analyzed Knodus species. The description of this new species fits the approach of the integrative taxonomy, since it is based on morphological data and six molecular species delimitation methods. The six molecular approaches are based on independent and different assumptions and calculations, making the hypothesis of the validity of the new species more robust. The use of different sources of investigation (morphology, molecular, geographic distribution, etc.) can help to identify groups with high morphological similarity, avoiding identification errors and, consequently, helping to solve problems of validity and positioning of taxonomic groups.